ANALYSIS OF FARMERS' PARTICIPATION IN THE RICE FARMING INSURANCE PROGRAM (AUTP) IN SILAU RAKYAT VILLAGE, SEI RAMPAH DISTRICT, SERDANG BEDAGAI DISTRICT - Eva Wardah; Adhiana; Setia Budi; Zulfathi Sidhqi (PT. Radja Intercontinental Publishing, 2024)
The agricultural sector is always faced with risks and uncertainties that can harm farmers. Therefore, there is a need for systematic and institutionalized efforts to reduce these risks and uncertainties, namely through agricultural insurance. This study aims to analyze the factors that influence farmers' participation in the AUTP program. This study involved 60 respondents. To analyze the level of farmers' participation in AUTP program, it is calculated using Likert Summated Rating scale and to analyze the factors influencing farmers' participation in AUTP program using multiple linear analysis method. The results of the study show that the factors that influence farmers' participation in the AUTP program in Silau Rakyat Village, simultaneously all independent variables have a significant effect on the dependent variable. However, partially, only the variables of income, farming experience, AUTP information, program benefits, and frequency of crop failure have a significant effect on farmers' participation in the AUTP program, while the variables of land area, socialization, and frequency of socialization have no significant effect on farmers' participation in the AUTP program in Silau Rakyat Village.